Isolation and application of bacteriophages as an antimicrobial alternative against beef-borne pathogens - García-Ponce, R.; Hernández-Escareño, J.J.; • Espinosa-Carranza, N.N.; Villarreal-Villarreal, J.P.; Hernández-Vidal, G. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
Meat products are widely consumed worldwide. During their production chain, they can be contaminated by pathogens such as Salmonella enterica subsp. enterica serovar Typhimurium and Escherichia coli, which cause serious and, in some cases, fatal infections. The limitations of conventional disinfection methods, together with the increasing resistance to antibiotics, underline the need for effective and economical alternatives. In this context, the use of phages as antimicrobial agents emerges as a promising solution. In this study, phages specific against strains of E. coli (ATCC 25922, 15597, 35401, O157:H7 ATCC 43888) and Salmonella Typhimurium (ATCC 13311) were obtained from water samples from a local wastewater treatment plant. Nineteen bacteriophages were isolated for E. coli strains, of which the E. coli strain ATCC 25922 showed higher susceptibility to the action of phages present in the water samples, while the strain ATCC 43888 showed high resistance. In the case of S. Typhimurium, only one phage (φ101) was isolated and evaluated against 30 clinical isolates of Salmonella spp., in which it showed lytic activity in 16. This same phage was used to reduce the bacterial load on a stainless-steel surface contaminated by S. Typhimurium, achieving a significant decrease after 24 hours. The results of this study highlight the potential antimicrobial activity of bacteriophages against antibiotic-susceptible and antibiotic-resistant strains, as well as their use as surface disinfectants. These findings suggest that the use of phages could represent an effective alternative for the treatment of pathogens transmitted by meat products.